2001
DOI: 10.1002/1522-2683(200106)22:10<2046::aid-elps2046>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and alkylation of proteins in preparation of two-dimensional map analysis: Why, when, and how?

Abstract: The standard procedure adopted up to the present in proteome analysis calls for just reduction prior to the isoelectric focusing/immobilized pH gradient (IEF/IPG) step, followed by a second reduction/alkylation step in between the first and second dimension, in preparation for the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) step. This protocol is far from being optimal. It is here demonstrated, by matrix assisted laser desorption/ionization-time of flight (MALDI-TOF)-mass spectrometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 226 publications
(136 citation statements)
references
References 26 publications
4
127
0
2
Order By: Relevance
“…Thiourea might have enhanced the solublization of the membranes or highly hydrophobic proteins in our samples, especially after mild sonication [22]. The solublization of membrane proteins is still the most challenging step in 2-DE-based proteomics approaches [23][24][25]. Nevertheless, the optimized protocol in this study resulted in a uniform spot distribution on a single protein map and we observed excellent reproducibility (Fig.…”
Section: -De Protocol and Reproducibilitymentioning
confidence: 67%
“…Thiourea might have enhanced the solublization of the membranes or highly hydrophobic proteins in our samples, especially after mild sonication [22]. The solublization of membrane proteins is still the most challenging step in 2-DE-based proteomics approaches [23][24][25]. Nevertheless, the optimized protocol in this study resulted in a uniform spot distribution on a single protein map and we observed excellent reproducibility (Fig.…”
Section: -De Protocol and Reproducibilitymentioning
confidence: 67%
“…The samples were loaded onto the target plate using the three layers method (19). 0.6 l of matrix solution (10 mg/ml sinapinic acid in 60% acetonitrile, 40% water, 0.1% trifluoroacetic acid, prepared fresh every day) were loaded onto the sample plates and left to dry at room temperature.…”
Section: Two-dimensional Gel Electrophoresis and Gel Staining-proteinmentioning
confidence: 99%
“…Homogenates were left in lysis buffer for 1 h and centrifuged at 14 000 r.p.m. Supernatants were collected, reduced and alkylated prior to isoelectrofocusing as previously described, 39 lyophilized, resuspended in rehydration buffer and stored at À801C until the isoelectrofocusing procedure. To release the DNA-bound/detergent-insoluble PCNA fraction, neoplastic and cirrhotic sample pellets were digested with DNAse-I as previously reported.…”
Section: Materials and Methods Patients And Tissue Collectionmentioning
confidence: 99%